2018
DOI: 10.5964/jspp.v5i2.705
|View full text |Cite
|
Sign up to set email alerts
|

A cultural psychological analysis of collective memory as mediated action: Constructions of Indian history

Abstract: The present research applies a cultural psychological perspective on collective memory as mediated action to examine how constructions of a national past serve as tools that both reflect and shape national identity concerns. We employ a situation-sampling method to investigate collective memory in a series of studies concerning intergroup relations in the Indian context. In Study 1, participants (N = 55) generated three historical events that they considered important/relevant for Indian history. In Study 2, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
1
8
0
1
Order By: Relevance
“…Follow‐up studies documented the consequences of engagement with different categories of historical facts. Consistent with the other studies that we have reviewed in this section, perception of injustice in Indian society was greater among participants who interacted with CHC representations that mentioned instances of collective wrong‐doing than among participants who interacted with more standard representations consisting of nation‐glorifying events (Mukherjee et al, ; Studies 3 and 4).…”
Section: Empirical Research: Group Differences In Perception Of Racismsupporting
confidence: 86%
See 3 more Smart Citations
“…Follow‐up studies documented the consequences of engagement with different categories of historical facts. Consistent with the other studies that we have reviewed in this section, perception of injustice in Indian society was greater among participants who interacted with CHC representations that mentioned instances of collective wrong‐doing than among participants who interacted with more standard representations consisting of nation‐glorifying events (Mukherjee et al, ; Studies 3 and 4).…”
Section: Empirical Research: Group Differences In Perception Of Racismsupporting
confidence: 86%
“…Although White American students in the study of Thanksgiving holiday commemorations generally indicated greater preference and relevance of official proclamations that failed to mention either Indigenous Peoples or genocidal violence, this tendency was particularly prominent among participants who scored high on a measure of national glorification or for whom an experimental manipulation made national glorification salient (Kurtiş et al, , Study 2). Similarly, although Indian participants rated liking and relevance for Indian history to be greater for nation‐glorifying collective triumphs than for more critical incidents of collective wrongdoing, this tendency was especially pronounced among participants who scored higher on a measure of national identification (Mukherjee et al, ; Study 2).…”
Section: Empirical Research: Group Differences In Perception Of Racismmentioning
confidence: 99%
See 2 more Smart Citations
“…i) The role of primary handling editor for each of the manuscripts present in this special thematic section was as follows: Ana Figueiredo -Brasil & Cabecinhas (2017), Mukherjee et al (2017), Kello (2017), Roth et al (2017) and Cheung et al (2017). Jonas Rees - Smeekes et al (2017), Martinovic et al (2017) and Andrighetto et al (2017).…”
Section: Notesmentioning
confidence: 99%